Hubungan kualitas informasi repositori ilmiah nasional dengan tingkat kepuasan di Lembaga Ilmu Pengetahuan Indonesia Bandung - Alwi Alfiana; Edwin Rizal; Rully Khoirul Anwar (Perpustakaan Universitas Gadjah Mada, 2021)
Introduction. The development in the field of information technology is growing rapidly from time to time. Digital-based repositories are a form of the use of information technology. Therefore, this study focuses on knowing the extent to which an information source such as a repository has a quality system that is able to produce quality information so as to provide satisfaction to its users. Research methods. This study used a correlational study method with a quantitative approach. The population were users of the National Scientific Repository, namely LIPI researchers in the Bandung area. Data Analysis. This study used a descriptive and inferential statistical analysis using the Spearman Rank test with SPSS application. Analysis Data. The results showed that the information quality variable has a significant relationship with the level of user satisfaction of the National Scientific Repository. Results and Discussion. The results of the study provide an illustration that the information quality variable has a significant relationship with the level of user satisfaction of the National Scientific Repository. Conclusions and Suggestions. This study shows that the system of National Scientific Repository is able to provide quality to the information provided, that having an impact on the level of satisfaction of the users of National Scientific Repository itself. Information quality should consider several dimensions such as time, content and format.